Implementation of management tools in non-profit organizations: a bibliometric analysis of the literature - Garcia Peñaloza, John Edisson (2025)
Non-profit organizations must balance financial sustainability with their social commitment, which requires strategic management involving various stakeholders, positioning them as key players in several economic sectors. The objective of this research is to analyze publication trends related to the use of management tools in non-profit entities. This study employed a mixed research approach, incorporating both quantitative and qualitative methods. It was based on a bibliometric study complemented by a document review of the SCOPUS, Google Scholar, and SciELO databases, covering the period from 1997 to 2024. The publication trends were heterogeneous, with a peak of four studies in a single year. Research articles in the fields of management, business, and accounting predominated, with the United States being the most productive country. A co-occurrence analysis of keywords allowed for the identification and description of five potential lines of scientific research addressed in the reviewed studies. The study concludes that the choice of management approach should align with the type of organization, ranging from private companies to non-profit institutions and government agencies, each possessing unique characteristics that influence their management strategies.